Tulevaisuuden työmarkkinat; Future Labour Markets - Antti Kauhanen (The Research Institute of the Finnish Economy (ETLA), 2014)
– Information and communications technology, global value chains, and population ageing are changing the structures of the labour market. These three factors affect the tasks carried out in Finland in the future and the division of labour between humans and computers. The changes are taking place at the individual level and affect the ways of working and income inequality. This report surveys the economic literature on these topics.
Keywords: J21; J24; J62; F16; 330; ICT; Global value chains; Population ageing; Structural change; Arbeitsmarkt; Strukturwandel; Bibliometrie; Finnland